The use of technologies to aid the treatment of Diabetes Mellitus: a study conducted with academics of the education center of the Alto Vale do Itajaí (Revista Brasileira de Contabilidade e Gestão, 2013)
This work aims to verify the feasibility of using an application to assist in the monitoring of type I and II Diabetes Mellitus. To achieve this goal, quantitative research was used, where students from the courses of Accounting, Sanitary Engineering, and Information Systems of the Center for Higher Education of Alto Vale do Itajaí (CEAVI) – UDESC were used as a sample. This research addressed issues related to the disease, such as knowledge, forms of treatment, and family members who have the disease. A total of 210 questionnaires were applied to the students, 70 of each course. Data analysis showed that no academic has the disease. Most academics answered that they have knowledge about the disease and would use an application to assist them in monitoring.
Keywords: Diabetes Mellitus; technology; monitoring